In-depth Exploration of ‘Tafakkur’ Through the Spirit of Quranic Verses - Zaini, Muhammad; Fauziah, Mira (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
This study aims to elucidate the multi-dimensional aspects of 'tafakkur' as depicted in the Quran, highlighting its implications for understanding the holistic integration of intellect and spirituality in Islamic teachings. Employing descriptive analytical methods, this study examines terms related to 'tafakkur' found in the Quran. The analysis identifies a rich framework of terms interconnected with 'tafakkur', demonstrating the Quran’s comprehensive approach to employing intellect and reason. Notably, 'tafakkur' is depicted not just as a cognitive activity but as a spiritual and moral duty essential for the full realization of Tawhid. 'Tafakkur' significantly enriches the Islamic intellectual tradition, emphasizing that true understanding of divine unity requires active and profound contemplation. This study reaffirms the critical role of reasoned faith and intellectual freedom in Islam.